Assessing the prevalence of iron deficiency anemia and risk factors among children and women: A case study of rural Uttar Pradesh - Jyoti Sharma; Sriram Devanathan; Angan Sengupta; P.N. Rajeshwari (Elsevier, 2024)
Background: Anemia, defined as low blood haemoglobin (Hb) concentration, is a serious global health problem that relates to negative health outcomes. Anemia is a sign of poor nutrition and primarily affects children, women of childbearing age, and pregnant women. Methods: A mixed method approach was used to collect data using a multilevel sampling technique from Nagla Chandi Village, Uttar Pradesh. Survey was conducted on thirty mothers of children aged 6-59 months and thirty-three reproductive age women. Qualitative data was collected from school teachers and one ASHA worker. Results: Community level anemia prevalence among women was similar to the NFHS statistics, while that of children was found to be lower in the studied community. In instances involving women, the prevalence of anemia was 64.7%, and the rates of mild and moderate anemia were 20.6% and 14.7%, respectively. Thirty-six percent of male and 44% female children were anemic. Seventy percent of male and 79% of female children were underweight. In case of adult females 18% were underweight and 26% were overweight. The risk factors of IDA and malnutrition are unhealthy eating habits, lack of intake of IFA supplements by women, lack of proper education in society, absence of Anganwadi (type of rural childcare centre in India), untreated water intake and poor hygiene practices are the major cause of IDA in this community. Conclusions: Food fortification, nutritional education, and good hygiene practices are prescribed interventions, to be implemented by Government bodies for the prevention of anemia.